2019
DOI: 10.3390/rs11161900
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Resolution Population Mapping from International Space Station Nighttime Photography and Multisource Social Sensing Data Based on Similarity Matching

Abstract: Previous studies have attempted to disaggregate census data into fine resolution with multisource remote sensing data considering the importance of fine-resolution population distribution in urban planning, environmental protection, resource allocation, and social economy. However, the lack of direct human activity information invariably restricts the accuracy of population mapping and reduces the credibility of the mapping process even when external facility distribution information is adopted. To address the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…RF is an integrated learning algorithm of bagging algorithm and decision tree algorithm, which can fit the complex nonlinear relationship between independent variables and dependent variables (Wang, Fan & Wang, 2019). The major parameters in this algorithm were set as follows: the scale was set as "TRUE", and the number of trees (ntree) was set as 500, the number of features tried at each node (mtry) depends on the lowest out-of-bag error.…”
Section: Model Construction and Validationmentioning
confidence: 99%
“…RF is an integrated learning algorithm of bagging algorithm and decision tree algorithm, which can fit the complex nonlinear relationship between independent variables and dependent variables (Wang, Fan & Wang, 2019). The major parameters in this algorithm were set as follows: the scale was set as "TRUE", and the number of trees (ntree) was set as 500, the number of features tried at each node (mtry) depends on the lowest out-of-bag error.…”
Section: Model Construction and Validationmentioning
confidence: 99%
“…With the increase in the availability of geospatial big data that are highly correlated with human activities, detailed estimations of coastal population exposure are possible. For example, previous studies showed the considerable potential of point-of-interest (POI) [9,10] and Sina Weibo check-in data [11] in high-resolution population mapping.…”
Section: Introductionmentioning
confidence: 99%
“…To some extent, night-time light data can compensate for the lack of panel statistical data in urban space research. Moreover, night-time light data can be applied in the study of urban space [11] because urban activities are closely correlated with electricity consumption [12], and many studies have proven that the intensity of urban light has a high correlation with urban population distribution [13]. Therefore, night-time light data are currently mainly used in urban expansion [14], urban morphology and structure [15], and social and economic status decisions [16].…”
Section: A Research On Night-time Light Datamentioning
confidence: 99%